Redescription and new records of Phoroncidia septemaculeata O. Pickard Cambridge 1873 from India (Araneae: Theridiidae) - Nafin, Karunnappilli Shamsudheen; Sumesh, Njarekkattil Vasu; Sudhin, Puthoor Pattammal; Sudhikumar, Ambalaparambil Vasu (Zootaxa, 2019)
The genus Phoroncidia Westwood 1835 is currently represented by 81 species and is cosmopolitan in distribution. Currently, four species are known from India, namely Phoroncidia aculeata Westwood 1835, Phoroncidia maindroni (Simon 1905), Phoroncidia septemaculeata O. Pickard-Cambridge 1873 and Phoroncidia testudo (O. Pickard-Cambridge 1873) (World Spider Catalog 2019). P. septemaculeata O. Pickard-Cambridge 1873 was described based on a few specimens collected by Mr G. H. K. Thwaites in 1871 from Sri Lanka and it was mostly derived from the somatic features of the species. Recently, Patil et al. (2018) reported two subadult males presumed to be Phoroncidia septemaculeata from the Maharashtra state in India. Until now, no mature specimen of the species has been reported and its genitalia remains unknown. This paper provides a detailed redescription of P. septemaculeata, including illustrations of male and female genitalia for the first time, based on fresh materials collected from different localities in the Coastal Plains and Western Ghats of Kerala state and Coastal plains of Tamil Nadu. Additionally, the current distributional range and new records of the species is mapped.